Dinamika Religiositas Pada Pengikut Komunitas Punk - Santi Andika Pratiwi; Firda Imah Suryani (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Many people think that Punk is a deviant behavior, synonymous with violence, a lifestyle that is free, chaotic and unsettling for society. But, Punk followers have sides of religiosity. This study aims to determine the religiosity of the Punk followers, in order to change the negative stigma of the surrounding community. This study used a qualitative method using a phenomenological approach. This study used five subjects with a purposive sampling technique with the following criteria: Punk followers aged 10-24 years of age, have never been the subject of previous research, and are still active in Punk activities. The results show that Punk child also have a side of religiosity even with their respective portions. From them, they have the hope of trying to fulfill their obligation to live spiritually to become a Punk followers and want to live a normal life again without any negative stigma. Thus, this study is expected to change the negative stigma of society about Punk.Â